2014
DOI: 10.1128/aem.00006-14
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Metal Ions on Stability and Activity of Hyperthermophilic Pyrolysin and Further Stabilization of This Enzyme by Modification of a Ca 2+ -Binding Site

Abstract: Pyrolysin is an extracellular subtilase produced by the marine hyperthermophilic archaeon Pyrococcus furiosus. This enzyme functions at high temperatures in seawater, but little is known about the effects of metal ions on the properties of pyrolysin. Here, we report that the supplementation of Na ؉ , Ca 2؉ , or Mg 2؉ salts at concentrations similar to those in seawater destabilizes recombinant pyrolysin but leads to an increase in enzyme activity. The destabilizing effect of metal ions on pyrolysin appears to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…Instead, Arg 249 appears to form unfavorable electrostatic interactions that destabilize pyrolysin. Our previous study showed that Asn substitutions at the Ca2 site residues Asp 818 and Asp 820 in pyrolysin enhances the thermostability of the enzyme (15). When incubated at 95°C, the variants R249E and D818N/D820N had a similar half-life of approximately 18 h, which is longer than that of the WT (approximately 12 h) (Fig.…”
Section: Figmentioning
confidence: 96%
See 4 more Smart Citations
“…Instead, Arg 249 appears to form unfavorable electrostatic interactions that destabilize pyrolysin. Our previous study showed that Asn substitutions at the Ca2 site residues Asp 818 and Asp 820 in pyrolysin enhances the thermostability of the enzyme (15). When incubated at 95°C, the variants R249E and D818N/D820N had a similar half-life of approximately 18 h, which is longer than that of the WT (approximately 12 h) (Fig.…”
Section: Figmentioning
confidence: 96%
“…Salt-induced autocleavage within IS29 and IS27 produces nicked pyrolysin. We showed previously that pyrolysin undergoes autocleavage when supplemented with various salts (15). Here, the cleavage sites were identified by N-terminal sequencing.…”
Section: Figmentioning
confidence: 99%
See 3 more Smart Citations